Posconflicto y discriminación laboral de excombatientes. Propuestas desde la teoría de la legislación y la responsabilidad social empresarial (2016)
This research aimed to analyze from the theory of legislation, supported by the Corporate Social Responsibility ( CSR ), proposals for intervention to situations that enhance employment discrimination of former combatants in post-conflict. With its development could be identified two key areas for the establishment of the proposals: the Legislative development from the legal framework for peace and the legal framework of reintegration; and effective private sector involvement in building peace through reintegration and CSR.